The effects of physical and temporal certainty on human locomotion with discrete underfoot perturbations - Kreter, N.; Lybbert, C.; Gordon, K. E.; Fino, P. C. (Journal of Experimental Biology, 2022)
Foot placement can be selected to anticipate upcoming perturbations, but it is unclear how this anticipatory strategy is influenced by available response time or precise knowledge of the perturbation's characteristics. This study investigates anticipatory and reactive locomotor strategies for repeated underfoot perturbations with varying levels of temporal certainty, physical certainty, and available response time. Thirteen healthy adults walked with random underfoot perturbations from a mechanized shoe. Temporal certainty was challenged by presenting the perturbations with or without warning. Available response time was challenged by adjusting the timing of the warning before the perturbation. Physical certainty was challenged by making perturbation direction (inversion or eversion) unpredictable for certain conditions. Linear-mixed effects models assessed the effect of each condition on the percentage change of margin of stability and step width. For perturbations with one stride or less of response time, we observed few changes to step width or margin of stability. As response time increased to two strides, participants adopted wider steps in anticipation of the perturbation (P=0.001). Physical certainty had little effect on gait for the step of the perturbation, but participants recovered normal gait sooner when the physical nature of the perturbation was predictable (P<0.001). Despite having information about the timing and direction of upcoming perturbations, individuals do not develop perturbation-specific feedforward strategies. Instead, they use feedback control to recover normal gait after a perturbation. However, physical certainty appears to make the feedback controller more efficient and allows individuals to recover normal gait sooner.